Uniões intra e inter-raciais, status marital, escolaridade e religião no Brasil: um estudo sobre a seletividade marital feminina, 1980-2000 - Luciene Aparecida Ferreira de Barros Longo (2011)
The objective of this dissertation is to verify if there is an association between racial endogamy and exogamy in Brazil and two sociodemographic characteristics, education and religion, based on data from demographic censuses of 1980, 1991 and 2000. Specifically, the objectives are to identify whether the female marital selectivity by race/ color is based on the compensation of racial differences by differences in characteristics such as education or religious affiliation. The analysis is performed for all women 20 to 29 years and their husbands/partners, differentiating formally married women and those in consensual union, using Log-linear models. The results point to major changes in the composition of unions in recent decades. There is a process of decline in racial endogamy already noted between 1980 and 1991, intensified in 2000. It can be argued further that there is a significant association between skin color and education of each spouse, and there is also an association between race and religious affiliation. However, how these associations occur is different. In the case of schooling, an individual of a race or color of lower social status (darker skin) is more likely to join a partner of one race or color of higher social status (lighter skin) when the differences in levels of schooling will outweigh these racial differences. Regarding religion, it is not possible to say that religious affiliation is an exchangeable feature for the racial differences between the partners. However, religion has a considerable power over the choices of partners, because having the same religion is a feature which encourages either the same race as interracial unions. This work advances in research on marital status and shows that, although from a legal standpoint, the differences between formal and informal unions have been minimized or even mitigated, there is still quite relevant and precise differences that may be hiding other differences of partners choice. The uniqueness of this investigation about racial endogamy and exogamy associated with religion, and also the aspects related to the marital status of those unions, shows the great power that religion still has on families.